Vicarious habitation – reinterpreting the role of peripheral living in a Nordic context. Issue 2 (1st February 2018) - Knudsen, Jon P.
ABSTRACT: This article argues that some of the contemporary attention given to sustaining habitation of regions and communities beyond capacity and prospects of economic growth can be understood by introducing the concept of 'vicarious habitation'. By this term is understood 'the notion of rural habitation performed by an active minority but on behalf of a much larger number, who (implicitly at least) not only understand, but, quite clearly, approve of what the minority is doing'. In many late modern societies, a substantial portion of the population seems willing to pay symbolically and politically to let a minority act on their behalf as caretakers of rural peripheries left behind by structural transformations. Signs of vicarious habitation occur that may vary in form and importance from country to country. Empirically, the argument is substantiated by Norwegian examples.